Exclusive Breastfeeding Practice and Associated Factors among Mothers in Boditi Town, Wolaita Zone, Southern Ethiopia, 2018: A Community-Based Cross-Sectional Study - Gedion Asnake Azeze; Kelemu Abebe Gelaw; Natnael Atnafu Gebeyehu; Molalegn Mesele Gesese; Taklu Marama Mokonnon (International Journal of Pediatrics)
Background. Exclusive breastfeeding tops the table of life-saving interventions for newborns. A child who is exclusively breastfed is 14 times less likely to die in the first six months compared to its counterpart. Approximately 18,000 children globally still die every day and if current trend continues, some 60 million children under age 5 will die between 2017 and 2030, and half of them will be newborns. Five countries, including Ethiopia, accounted for half of all newborn deaths in the world. Objective. To assess the prevalence and associated factors of exclusive breastfeeding practice among mothers who have infants 6-12 months of age in Boditi Town, Wolaita Zone, Southern Ethiopia, 2018. Methods. Community-based cross-sectional study was conducted among 412 randomly selected mothers having 6 to 12 month infants from April 1 to 14, 2018. A pretested interviewer administered questionnaire was used for data collection. The data were entered using Epi Data version 3.1 and analyzed using SPSS version 20. Descriptive statistics was made. Bivariate and multivariate logistic regression was also carried out to see the effect of each independent variable on the dependent variable. Results. Of 412 mother-infant pairs sampled, 403 were participated, which made a response rate of 97.8%. Prevalence of EBF computed using since birth dietary recall method was 64.8% (95% C.I= 60.0, 69.0). From multivariable analysis, child birth attended by health care provider (AOR = 5.303, 95% C.I = 1.613, 17.436), postnatal care utilization (AOR = 1.91, C.I = 1.083, 3.370), and mothers who did not report any breast related problem for the first six months after child birth (AOR = 1.864, C.I = 1.090, 3.189) were factors positively associated with exclusive breastfeeding practice. Conclusion. Although the prevalence of exclusive breastfeeding practice in this study was relatively high, more effort to meet World Health Organization (WHO) recommendations is still necessary to benefit from its intervention. There is a need to promote child births to be attended by health care providers and postnatal care utilization. Further, women should be educated on what to do and where to seek care if breast problem occurs after child birth.